Features of the development of print media in the United States: Features of the development of print media in the United States - Akseiit, Ғ.М.; Kabdugaliev, А.К. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2022)
The article deals with the genesis - the history of the birth - of printed mass media in the United States of America (USA). The article reveals features of evolution and the reasons for the rise and fall of newspaper publications against the background of the formation and development of American statehood. The article considers the current state of the US media industry, the change in the role of traditional media in the digital age, and the problem